Oral manifestations in patients with chronic hepatitis C - Michał Brzdęk; Joanna Gałuszka-Garnuszek; Krystyna Dobrowolska; Kinga Brzdęk; Jakub Janczura; Olga Tronina; Magdalena Kal; Piotr Stępień; Dorota Zarębska-Michaluk (BMC Oral Health)
Abstract Background Hepatitis C virus (HCV) infection, a systemic disease characterized by extrahepatic manifestations (EMs), affects approximately 50 million people worldwide. Recognizing EMs, which may involve multiple organs and systems, is crucial for timely diagnosis and effective antiviral therapy. Purpose of the study was to investigate extrahepatic symptoms occurring in the oral mucosa in HCV-infected patients. Methods The observational study included 153 consecutive patients with chronic hepatitis C and healthy controls. Data collection encompassed demographic parameters, medical history, laboratory results, and oral examinations, which included evaluation of dry mouth, pain and burning in the mouth and on the tongue, pain in the angles of the mouth, bad breath, gingival bleeding, dysphagia and taste disorders using scales designed for this purpose, clinical and dental examination. Results Subjective oral symptoms were twice as common in the study group as in controls with the most frequent dry mouth, followed by oral pain, and burning in the mouth. Pathological changes (oral candidiasis, angular cheilitis and lichen planus), were identified in 73.2% of patients, compared to 32% in the control group. Oral hygiene was worse in the study group with a median score of 1.8 compared to 1.1 as assessed by the Oral Hygiene Index scale. The incidence of Mikulicz's aphthae, papillomas, fibromas and sublingual varices did not reach statistically significant differences. The study group had fewer teeth with dental fillings. Additionally, age ≥ 40 years and GT1 infection were identified as independent predictors of oral pathologies in HCV-infected patients. Conclusions In patients with chronic HCV infection, oral mucosal pathologies were significantly more common compared to controls, with candidiasis, angular cheilitis, and oral lichen planus being the most frequently observed conditions. Subjective symptoms such as dry mouth, oral pain, and burning were also markedly higher in the HCV group. Age ≥ 40 years and GT1b HCV genotype were identified as independent positive predictors of oral mucosal lesions.